Architectural Psychology and Communication in Designing Spatial Layouts - Sri Prasetyo Widodo; Edison Hatoguan Manurung; Mira Nurul Huda; Oskar Royke Muntu; Penanga Octavianews; Siti Sa’Ani; Wisnu Pamungkas; Wiwin Wandri; Muji Indarwanto; Suripto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Each individual's intellectual, physical, and psychological personality is influenced and formed by the arrangement of their workstation. A pleasant work environment may enhance the psychological and communicative performance of employees, hence increasing productivity. The psychological aspect of a person's mental health is caused by an environment with an acceptable and relaxing arrangement, so as to contribute to the psychological serenity of communication. This study was undertaken at Mpu Tantular University through Community Service Program (KKN) activities conducted by college students using the devotion approach via renovation of the engineering and communication science faculties room. In this study, the secondary data sources consist of scientific journal articles and previously completed research results. This is accomplished through Google search and Emerald Publishing as well as national and international journals.